Silicon-carbon composite material and preparation method thereof, pole piece and application thereof, and electrochemical device

By performing magnesium thermal reaction under the gas phase system, controlling the deposition position of silicon in porous carbon, the shortcomings of existing silicon-carbon composite materials in improving circulation performance are solved, and better circulation performance and mechanical stability of lithium-ion batteries are achieved.

CN119797320AActive Publication Date: 2025-04-11SHANGHAI SHANSHAN NEW MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411997998.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing silicon-carbon composite materials have shortcomings in silicon deposition position control, resulting in the cycling performance of lithium-ion batteries not being effectively improved.

Method used

The magnesium thermal reaction is carried out under the gas phase system to control the deposition position of the silicon, thereby forming an effective silicon particle-encapsulated magnesium oxide structure in the porous carbon to alleviate the stress caused by the expansion of the silicon volume.

Benefits of technology

By effectively controlling the deposition position of silicon, the circulation performance of lithium-ion batteries is significantly improved, and the mechanical stability and charge and discharge efficiency of the batteries are enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a silicon-carbon composite material and a preparation method thereof, a pole piece and application thereof, and an electrochemical device. The preparation method of the silicon-carbon composite material comprises the following steps: depositing mixed gas in porous carbon, and then carrying out carbon coating; the mixed gas comprises magnesium in a gas form and a silicon source; in the mixed gas, the mass ratio of the magnesium to the silicon source is (0.5-2): 1, and the silicon source comprises silicon oxide. The magnesiothermic reaction is carried out under the gas phase system, so that the deposition position of silicon can be effectively controlled. The battery prepared from the silicon-carbon composite material disclosed by the invention has relatively good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a silicon-carbon composite material and a preparation method thereof, a pole piece and application thereof, and an electrochemical device. Background Art

[0002] Silicon-based materials are abundant in reserves, relatively low in cost, and environmentally friendly. They have a high theoretical specific capacity and can significantly increase the single cell capacity of lithium-ion batteries, thereby increasing the energy density of the battery, making it possible to achieve high energy density and long-lasting lithium-ion batteries. Silicon undergoes a huge volume expansion (up to 300% or more) during the charging and discharging process, causing the electrode material to pulverize and fall off, which in turn causes the rapid attenuation of the battery capacity and poor cycle performance. This is a key issue limiting the large-scale application of silicon-based negative electrode materials. In addition, silicon has relatively poor conductivity, which will also affect the rate performance of the battery.

[0003] Porous carbon has a rich pore structure and a large specific surface area, which can provide a large number of active sites, which is conducive to the deposition and dispersion of silicon, increases the contact area between silicon and electrolyte, and improves the charge and discharge efficiency of the battery. At the same time, the pore structure of porous carbon can provide a buffer space for the volume expansion of silicon during the charge and discharge process, effectively alleviate the volume effect of silicon, reduce the pulverization and shedding of electrode materials, and improve the cycle stability of the battery.

[0004] The presence of porous silicon can increase the flexibility of electrode materials. Compared with dense silicon materials, porous silicon can better adapt to changes in stress when the volume changes, and is less likely to crack and break, thereby improving the mechanical stability of the electrode during the charge and discharge cycle and helping to reduce the volume expansion caused by the destruction of the electrode structure.

[0005] Therefore, depositing porous silicon inside porous carbon can greatly reduce the volume expansion of silicon-based negative electrodes. For example, Chinese patent document CN 102569759 A discloses a method for preparing lithium-ion battery silicon-porous carbon negative electrode materials. The silicon-porous carbon composite material finally prepared has a nanoporous structure, which provides a certain buffer space for the volume expansion of silicon and can improve the cycle performance of the material. However, the material has poor control over the deposition position of silicon, which leads to the improvement of its cycle performance. Summary of the invention

[0006] The technical problem to be solved by the present invention is to overcome the defect that the silicon-carbon composite material in the prior art has poor control over the position of silicon deposition, resulting in the cycle performance of the battery made of the material still needs to be improved, and provide a silicon-carbon composite material and its preparation method, pole piece and application, and electrochemical device. The present invention can effectively control the deposition position of silicon by carrying out magnesium thermal reaction in a gas phase system. The battery made of the silicon-carbon composite material of the present invention has better cycle performance.

[0007] The present invention adopts the following technical solutions to solve the above technical problems.

[0008] The present invention provides a method for preparing a silicon-carbon composite material, which comprises the following steps:

[0009] The mixed gas is deposited in porous carbon and then carbon coated; the mixed gas includes magnesium and a silicon source in gaseous form; in the mixed gas, the mass ratio of magnesium to SiOx is (0.5-2):1, and the silicon source includes silicon oxide.

[0010] In the present invention, the chemical formula of the silicon oxide is generally SiOx, 0<x<2, preferably 0.8<x<1.2, for example, x is 1.

[0011] In the present invention, the silicon source preferably also includes silicon.

[0012] In the present invention, the mixed gas can be prepared by gasifying magnesium powder and silicon source powder separately and then mixing them.

[0013] The gasification temperature of the magnesium powder is preferably 300-900°C, more preferably 400-800°C, such as 500, 600 or 700°C.

[0014] The rate of heating from room temperature to the gasification temperature of the magnesium powder is preferably 3-7° C. / min, such as 4, 5 or 6° C. / min.

[0015] The gasification time of the magnesium powder may be 1-3 hours, for example 2 hours.

[0016] Wherein, the D50 particle size of the magnesium powder may be 3-7 μm, for example, 5 μm.

[0017] The gasification temperature of the silicon source powder is preferably 1300-190°C, more preferably 1500-1800°C, such as 1600°C.

[0018] The rate of heating from room temperature to the gasification temperature of the silicon source powder may be 3-7° C. / min, such as 4, 5 or 6° C. / min.

[0019] The gasification time of the silicon source powder may be 1-3 hours, for example 2 hours.

[0020] The gasification of the magnesium powder and the silicon source powder can be carried out in a rotary furnace, and preferably they are respectively arranged in two vacuum heating chambers in the rotary furnace.

[0021] In the silicon source powder, the atomic ratio of silicon to oxygen may be 1:(0.8-1.2), for example, 1: 1. The D50 particle size of the silicon source powder may be 3-7 μm, for example, 5 μm.

[0022] In the present invention, in the mixed gas, the mass ratio of magnesium to silicon source is preferably (0.52-1.80):1, such as 0.54:1, 1.09:1 or 1.63:1.

[0023] In the present invention, the porous carbon may be conventional in the art. The specific surface area of ​​the porous carbon may be 1800-2000m 2 / g. The pore volume of the porous carbon may be 0.7-0.9m 3 The D50 particle size of the porous carbon may be 7-9 μm.

[0024] In the present invention, the deposition can be carried out in a rotary furnace. The deposition is preferably carried out under a vacuum degree of 0.01-0.03Pa.

[0025] In the present invention, the deposition temperature may be 500-700°C, for example 600°C.

[0026] In the present invention, the rate of heating from room temperature to the deposition temperature may be 3-7° C. / min, such as 4, 5 or 6° C. / min.

[0027] In the present invention, the deposition time may be 8-12 hours, for example 10 hours.

[0028] In the present invention, the mass ratio of the porous carbon to the magnesium in the mixed gas may be 1:(0.5-1.2), preferably 1:(0.8-1.0), for example 1:0.86.

[0029] In the present invention, the mass ratio of the porous carbon to the silicon source in the mixed gas may be 1:(0.5-1.2), preferably 1:(0.6-0.9), for example 1:0.79.

[0030] In the present invention, after the deposition and before the gas phase carbon coating, a hydrochloric acid washing step is preferably performed. The molar concentration of the hydrochloric acid solution used in the hydrochloric acid washing can be 5-7 mol / L, for example, 6 mol / L. The hydrochloric acid washing time can be 1-5 hours, for example, 3 hours.

[0031] In the present invention, the carbon coating may be conventional in the art, and preferably includes liquid phase carbon coating and / or gas phase carbon coating, such as gas phase carbon coating.

[0032] Wherein, the gas phase carbon coating can be carried out in a rotary furnace.

[0033] The carbon source gas for gas-phase carbon coating may be conventional in the art, and preferably includes one or more of alkynes, alkanes, alkenes, aromatic compounds and carbohydrates, such as acetylene.

[0034] The temperature of the gas phase carbon coating may be 600-800°C, for example 700°C.

[0035] The gas phase carbon coating time may be 1-5 hours, for example 3 hours.

[0036] The rate of heating from room temperature to the temperature of the gas phase carbon coating may be 3-7°C / min, such as 4, 5 or 6°C / min.

[0037] The mass volume ratio of the porous carbon and the gas-phase carbon-coated carbon source may be 1 g:(0.1-0.2) L, for example, 1 g:0.18 L.

[0038] The present invention also provides a silicon-carbon composite material, which is prepared by the preparation method of the silicon-carbon composite material as described above.

[0039] In the present invention, in the silicon-carbon composite material, the mass content of magnesium may be 0.04%-30.1%, for example, 6.73%, 0.81%, 0.66%, 0.49%, 0.32%, 0.25%, 0.24%, 0.11% or 0.05%.

[0040] In the present invention, in the silicon-carbon composite material, the mass content of silicon may be 1.73%-30.7%, for example, 30.6%, 30.1%, 29.7%, 28.4%, 25.3%, 21.5%, 15.6% or 12.6%.

[0041] The present invention also provides a pole piece, which comprises the silicon-carbon composite material as described above.

[0042] The present invention also provides an application of the silicon-carbon composite material as described above in an electrochemical device.

[0043] The present invention also provides an electrochemical device, which comprises the pole piece as described above.

[0044] In the present invention, the electrochemical device is preferably a lithium ion battery.

[0045] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0046] The reagents and raw materials used in the present invention are commercially available.

[0047] The positive and progressive effects of the present invention are:

[0048] (1) The mixed gas in the present invention includes magnesium and silicon sources. The magnesium thermal reaction between magnesium and silicon dioxide in the silicon source will form a structure in which silicon particles wrap magnesium oxide. The magnesium thermal reaction in the gas phase system will make the generated structure more effectively deposited in the pores of porous carbon. The pore structure of porous carbon can well alleviate the volume expansion of silicon particles. Preferably, the silicon particles are further converted into porous silicon through subsequent selective washing. The special structure of porous silicon can further alleviate the stress caused by silicon expansion.

[0049] (2) The battery made of the silicon-carbon composite material of the present invention has better cycle performance. DETAILED DESCRIPTION

[0050] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.

[0051] Example 1

[0052] S1. Gasification process of magnesium powder and SiOx powder: 860g Mg powder (D50 is 5μm) and 790g SiOx powder (the atomic ratio of silicon and oxygen is 1:1, D50 is 5μm) are placed in two vacuum heating chambers of a rotary furnace respectively. The Mg powder chamber is heated to 600℃ at a heating rate of 5℃ / min, kept at a constant temperature for 2h, and then 2L / min nitrogen is introduced for 30min and then stopped for 30min. The SiOx powder chamber is heated to 1500℃ at a heating rate of 5℃ / min, kept at a constant temperature for 2h, and then 2L / min nitrogen is introduced for 30min and then stopped for 30min.

[0053] S2.(1) Deposition process: Weigh 1 kg of porous carbon (with a specific surface area of ​​1800-2000 m 2 / g, pore volume can be 0.7-0.9m 3 / g, D50 is 7-9μm) is placed in a rotary kiln, evacuated to 0.01Pa, and heated to 600℃ at a heating rate of 5℃ / min, and then the gasified magnesium and the gasified SiOx are respectively introduced into the rotary kiln through the outlet pipes of two vacuum heating cavities, and after the constant temperature is maintained for 10h, the gas source is turned off and 5L / min nitrogen is introduced; the mass ratio of the gasified magnesium Mg to the gasified SiOx is 1.09:1;

[0054] (2) then discharging the material under nitrogen conditions and acid washing with 6 mol / L hydrochloric acid for 3 h;

[0055] (3) The pickled material is then put back into the rotary kiln, heated to 700°C at 5°C / min, and then 1L / min of acetylene gas is introduced. After gas-phase carbon coating for 3 hours, the furnace is closed and then cooled and discharged.

[0056] Example 2

[0057] The only difference from Example 1 is that the amount of Mg powder added in S1 is changed to 430 g.

[0058] Example 3

[0059] The only difference from Example 1 is that the amount of Mg powder added in S1 is changed to 1290 g.

[0060] Example 4

[0061] The only difference from Example 1 is that the temperature of the Mg powder cavity in S1 is 400°C.

[0062] Example 5

[0063] The only difference from Example 1 is that the temperature of the Mg powder cavity in S1 is 800°C.

[0064] Example 6

[0065] The only difference from Example 1 is that the temperature of the SiOx cavity in S1 is 1800°C.

[0066] Example 7

[0067] The only difference from Example 1 is that the pickling time in S2(2) is 1 h.

[0068] Example 8

[0069] The only difference from Example 1 is that the pickling time in S2(2) is 5 h.

[0070] Example 9

[0071] The only difference from Embodiment 1 is that S2 (2) is omitted.

[0072] Comparative Example 1

[0073] The only difference from Example 1 is that no magnesium powder is added.

[0074] Comparative Example 2

[0075] The only difference from Example 1 is that SiOx is not added.

[0076] Comparative Example 3

[0077] The only difference from Example 1 is that the temperature of the SiOx cavity in S1 is 900°C. In Comparative Example 3, due to the low vaporization temperature of SiOx, silicon dioxide in the cavity cannot be completely vaporized, so the mass ratio of vaporized magnesium Mg to vaporized SiOx is greater than 1.09:1.

[0078] Comparative Example 4

[0079] The only difference from Example 1 is that the temperature of the silicon oxide cavity in S1 is 1200°C. In Comparative Example 3, due to the low vaporization temperature of SiOx, the silicon oxide in the cavity cannot be completely vaporized, so the mass ratio of vaporized magnesium Mg to vaporized SiOx is greater than 1.09:1.

[0080] Effect Example 1

[0081] The silicon-carbon composite materials prepared in the above examples or comparative examples were tested for element content.

[0082] The magnesium content was tested by an ICP analyzer; the test method was as follows: (1) pre-treatment by microwave digestion, 0.5 g of the silicon-carbon composite material prepared in the embodiment or the comparative example was placed in a digestion tank, 3 mL of concentrated nitric acid and 9 mL of concentrated sulfuric acid were added in sequence with a liquid adder, and the mixture was shaken well; and the mixture was kept at a constant temperature of 160°C for 3 min, 180°C for 3 min, 200°C for 10 min, and 220°C for 10 min, and then cooled to room temperature, filtered with quantitative filter paper, and the filtrate was placed in a 50 mL volumetric flask as the test solution; (2) the above test solution was placed in a PerkinElmer ICP spectrometer Avio TM The test was carried out in 200 equipment; the test condition was an air pressure of 2.5MPa.

[0083] The test method for silicon content is as follows: 20 g of the silicon-carbon composite material prepared in the above embodiment or comparative example is placed in a muffle furnace, heated to 1500° C. under oxygen conditions, and the mass of the material is weighed to calculate the silicon content.

[0084] The results are shown in Table 1.

[0085] Table 1

[0086] Magnesium content Silicon content Example 1 0.32 30.1 Example 2 0.11 25.3 Example 3 0.66 29.7 Example 4 0.04 21.5 Example 5 0.24 30.6 Example 6 0.25 30.7 Example 7 6.73 28.4 Example 8 0.05 30.7 Example 9 30.1 15.6 Comparative Example 1 0 21.7 Comparative Example 2 0.53 0 Comparative Example 3 0.81 1.73 Comparative Example 4 0.49 12.6

[0087] Effect Example 2

[0088] A mixture of the silicon-carbon composite material, a binder (sodium carboxymethyl cellulose, CMC; styrene-butadiene rubber, SBR) and a conductive agent (conductive carbon black, SP; single-walled carbon nanotube, SWCNT) prepared in the above embodiment or comparative example (wherein the mass ratio is, silicon-carbon composite material: SP: SWCNT: CMC: SBR = 90: 4.5: 0.5: 2.5: 2.5) is homogenized and coated on a copper foil, and vacuum dried, rolled and cut to obtain a negative electrode sheet. A metal lithium sheet is used as a counter electrode, and the electrolyte ratio is 1M LiPF6, 89% by volume of ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio of 1: 1), 10% by volume of fluoroethylene carbonate (FEC) and 1% by volume of vinylene carbonate (VC), and a polypropylene microporous membrane is used as a diaphragm, and a button-type half-cell is assembled in an inert gas glove box system filled with argon.

[0089] At 25°C, the assembled half-cell was tested for charge and discharge cycles using a blue electric test instrument to obtain data such as capacity, first coulomb efficiency, and cycle. The test procedure was 0.1C discharge to 5mV, 0.05C discharge to 5mV, 0.1C charge to 2V. The cycle format was: 0.5C discharge to 5mV, 0.05C discharge to 5mV, 0.5C charge to 1V.

[0090] The results are shown in Table 2.

[0091] Table 2

[0092] Reversible specific capacity (mAh / g) First coulombic efficiency (%) 500-week cycle retention rate (%) Example 1 1244 85.3 94.8 Example 2 957 81.9 82.3 Example 3 1189 83.4 91.2 Example 4 412 74.7 78.4 Example 5 1267 84.6 93.1 Example 6 1272 84.3 92.7 Example 7 1121 81.2 84.3 Example 8 1058 81.6 89.6 Example 9 794 73.9 82.4 Comparative Example 1 431 74.2 76.5 Comparative Example 2 164 21.9 37.7 Comparative Example 3 186 27.7 46.8 Comparative Example 4 447 68.1 57.2

[0093] As shown in Table 2, compared with Comparative Examples 1-4, in Examples 1-9, magnesium powder and silicon oxide powder are gasified at a specific temperature to obtain a first mixed gas, which is deposited in porous carbon and subjected to gas phase carbon coating to obtain a silicon-carbon composite material. Batteries made from the silicon-carbon composite materials obtained in Examples 1-9 have better first coulombic efficiency and cycle performance.

Claims

1. A method for preparing a silicon-carbon composite material, characterized in that: It includes the following steps: The mixed gas is deposited in porous carbon and then carbon coated; the mixed gas includes magnesium and silicon sources in gaseous form; in the mixed gas, the mass ratio of magnesium to silicon source is (0.5-2):1, and the silicon source includes silicon oxide.

2. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: A. The chemical formula of the silicon oxide is SiOx, 0<x<2; preferably, 0.8<x<1.2, for example, x is 1; B. The silicon source further comprises silicon; C. In the mixed gas, the mass ratio of magnesium to silicon source is (0.52-1.80):1, for example, 0.54:1, 1.09:1 or 1.63:1; D. The specific surface area of ​​the porous carbon is 1800-2000m 2 / g; E. The pore volume of the porous carbon is 0.7-0.9m 3 / g; F. The D50 particle size of the porous carbon is 7-9 μm.

3. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The method for preparing the silicon-carbon composite material meets one or more of the following conditions: A. The deposition temperature is 500-700° C., for example 600° C.; B. The rate of heating from room temperature to the deposition temperature is 3-7°C / min, such as 4, 5 or 6°C / min; C. The deposition time is 8-12 hours, for example 10 hours; D. The mass ratio of the porous carbon to the magnesium in the mixed gas is 1:(0.5-1.2), preferably 1:(0.8-1.0), for example 1:0.86; E. The mass ratio of the porous carbon to the silicon source in the mixed gas is 1:(0.5-1.2), preferably 1:(0.6-0.9), for example 1:0.

79.

4. The method for preparing the silicon-carbon composite material according to claim 2, characterized in that: The method for preparing the mixed gas includes gasifying magnesium powder and silicon source powder separately and then mixing them; wherein the method for preparing the mixed gas preferably satisfies one or more of the following conditions: A. The gasification temperature of the magnesium powder is 300-900°C, preferably 400-800°C, such as 500, 600 or 700°C; B. The rate of heating from room temperature to the gasification temperature of the magnesium powder is 3-7°C / min, for example 4, 5 or 6°C / min; C. The gasification time of the magnesium powder is 1-3 hours, for example 2 hours; D. The D50 particle size of the magnesium powder is 3-7 μm, for example 5 μm; E. The gasification temperature of the silicon source powder is 1300-190° C., preferably 1500-1800° C., for example 1600° C.; F. The rate of heating from room temperature to the gasification temperature of the silicon source powder is 3-7°C / min, for example 4, 5 or 6°C / min; G. The gasification time of the silicon source powder is 1-3 hours, for example 2 hours; H. The D50 particle size of the silicon source powder is 3-7 μm, for example 5 μm; I. The mixing is achieved by simultaneously introducing a gaseous magnesium source and a gaseous silicon source into a deposition device during the deposition process.

5. The method for preparing the silicon-carbon composite material according to claim 1, characterized in that: The carbon coating includes liquid phase carbon coating and / or gas phase carbon coating, preferably gas phase carbon coating; wherein the gas phase carbon coating preferably satisfies one or more of the following conditions: A. The temperature of the gas phase carbon coating is 600-800°C, for example 700°C; B. The gas phase carbon coating time is 1-5 hours, for example 3 hours; C. The rate of heating from room temperature to the temperature of the gas phase carbon coating is 3-7°C / min, such as 4, 5 or 6°C / min; D. The gas-phase carbon-coated carbon source includes one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene; E. The mass volume ratio of the porous carbon and the gas phase carbon-coated carbon source is 1 g: (0.1-0.2) L, for example 1 g: 0.18 L; And / or, after the deposition and before the gas phase carbon coating, a hydrochloric acid washing step is further performed; Wherein, the molar concentration of the hydrochloric acid solution used in the hydrochloric acid washing is preferably 5-7 mol / L, for example 6 mol / L; The hydrochloric acid washing time is preferably 1-5 hours, such as 3 hours.

6. A silicon-carbon composite material, characterized in that: The silicon-carbon composite material is prepared by the preparation method of any one of claims 1 to 5.

7. The silicon-carbon composite material according to claim 6, characterized in that: The silicon-carbon composite material meets one or more of the following conditions: A. In the silicon-carbon composite material, the mass content of magnesium is 0.04%-30.1%, for example, 6.73%, 0.81%, 0.66%, 0.49%, 0.32%, 0.25%, 0.24%, 0.11% or 0.05%; B. In the silicon-carbon composite material, the mass content of silicon is 1.73%-30.7%, for example, 30.6%, 30.1%, 29.7%, 28.4%, 25.3%, 21.5%, 15.6% or 12.6%.

8. A pole piece, characterized in that: It comprises the silicon-carbon composite material as claimed in claim 6 or 7.

9. Use of the electrode piece according to claim 8 in an electrochemical device.

10. An electrochemical device, characterized in that: It comprises the pole piece as claimed in claim 8.

Citation Information

Patent Citations

  • Composite material, preparation method thereof and lithium ion battery

    CN118016828A

  • Silicon-carbon composite negative electrode material and preparation method thereof

    CN118579791A

  • Porous silicon-based carbon composite, method for preparing same, and negative electrode active material comprising same

    US20230352665A1